Marketing Communications Mix in Sabang Tourism Promotion: Interaction of Political and Multicultural Communication - Rangga Saptya Mohamad Permana; Sri Seti Indriani; Lilis Puspitasari; Tito Quiling, Jnr. (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2026)
Sabang City as a Special Economic Zone (SEZ) and part of the Province of Nanggroe Aceh Darussalam (Aceh) has abundant tourism potential but faces challenges in optimal development and promotion. Sabang possesses significant tourism potential that requires effective communication strategies to attract both domestic and international visitors. This research examines the implementation of the marketing communication mix in promoting Sabang’s tourism and explores its political and multicultural dimensions. Using a descriptive–qualitative method, data were collected through interviews, observation, and document analysis. The findings show that Sabang’s tourism promotion utilizes various communication mix components, including advertising (outdoor media and digital platforms), events such as Sail Sabang, direct marketing through websites, word-of-mouth testimonials, and personal selling by local tourism agents. Beyond marketing functions, these practices also operate as political communication, projecting the government’s image of stability, openness, and development, while simultaneously facilitating multicultural interaction between Acehnese hosts and diverse visitors. The use of digital media further supports cultural hybridity by integrating local values with global tourism narratives. The research concludes that tourism promotion in Sabang represents not only strategic marketing but also a communicative process of image-building, intercultural understanding, and soft power representation. It is hoped that the resulting strategic recommendations can serve as a reference for local governments and tourism industry players in formulating more effective and impactful promotional policies.Keywords: Marketing communication mix, tourism promotion, political communication, multicultural communication, Sabang ABSTRAKKota Sabang sebagai Kawasan Ekonomi Khusus (KEK) dan bagian dari Provinsi Nanggroe Aceh Darussalam (Aceh) memiliki potensi pariwisata yang melimpah namun menghadapi tantangan dalam pengembangan dan promosi yang optimal. Sabang memiliki potensi pariwisata yang besar yang memerlukan strategi komunikasi efektif untuk menarik wisatawan domestik maupun mancanegara. Penelitian ini mengkaji penerapan bauran komunikasi pemasaran dalam promosi pariwisata Sabang serta menelusuri dimensi politik dan multikultural di dalamnya. Dengan metode deskriptif-kualitatif, data dikumpulkan melalui wawancara, observasi, dan telaah dokumen. Hasil penelitian menunjukkan bahwa promosi pariwisata Sabang memanfaatkan berbagai elemen bauran komunikasi, seperti periklanan (media luar ruang dan digital), kegiatan seperti Sail Sabang, pemasaran langsung melalui situs web, pemasaran dari mulut ke mulut, serta penjualan pribadi oleh agen wisata lokal. Lebih dari sekadar kegiatan pemasaran, praktik ini juga berfungsi sebagai komunikasi politik yang membangun citra pemerintah daerah sebagai wilayah yang stabil, terbuka, dan progresif, sekaligus menciptakan interaksi multikultural antara masyarakat Aceh dan wisatawan beragam budaya. Pemanfaatan media digital turut memperkuat hibriditas budaya melalui integrasi nilai lokal dan narasi pariwisata global. Penelitian ini menyimpulkan bahwa promosi pariwisata Sabang tidak hanya merupakan strategi pemasaran, tetapi juga proses komunikasi yang mencerminkan pembangunan citra, pemahaman antarbudaya, dan representasi soft power. Rekomendasi strategis yang dihasilkan diharapkan dapat menjadi acuan bagi pemerintah daerah dan pelaku industri pariwisata dalam merumuskan kebijakan promosi yang lebih efektif dan berdampak luas.Kata Kunci: Bauran komunikasi pemasaran, promosi pariwisata, komunikasi politik, komunikasi multikultural, Sabang